Trends and variability of rainfall seasonality indices in the Lao People’s Democratic Republic (PDR) - Atiah, Winifred A.; Muthoni, Francis K. (International Institute of Tropical Agriculture, 2023)
In rainfed agricultural systems, like in Lao PDR, where rainy season rainfall is a crucial water source for agricultural production, accurate prediction of the rainfall seasonality indices (onset, cessation, and LGP) is critical for agricultural planning. These indices determine the timing of land preparation, seeding, and transplanting of major crops, as well as the mobilization of seeds or crops. Accurate knowledge of the dates of rainfall seasonality indices reduces the risk of planting and sowing too late or too early. This study, therefore, used highly-resolved CHIRPS-V2 data to determine the climatologies, variability, and trends of the three seasonality indices over Lao PDR. Rainfall onset dates in Laos vary across regions. In eastern Xekong, they typically span from March 6 to March 21, while in areas bordering Vietnam, onsets are observed from March 21 to April 5. Northern Laos experiences onsets between April 5 and April 20, and in the southwestern LPDR areas, including Vientiane and Xaignabouri, beginnings occur from April 20 to May 5. Southern Champasak has late onsets from May 5 to June 4. Eastern Champasak and certain regions experienced rainfall cessation between August 31 and September 20. Conversely, Bokeo, Luang Namtha, and Phôngsali see cessation between October 10 and 20. For many of Laos, cessation occurs from September 20 to September 30, and the southeast has cessation dates from October 10 to October 30. Champasak and Attapu provinces have the shortest Length of Growing Period (LGP), spanning 110 to 130 days, while the western regions consistently exhibit shorter LGP (130 to 170 days), and the eastern half experiences longer LGP (170 to 230 days). Notably, LGP variability was consistently higher than onset and cessation dates. The trends analysis showed the Southern and Northeastern regions exhibit delayed onsets, while northwestern areas experience early onsets. Particularly early onsets are noted in parts of Khammouan. Northern-central regions and western Savannakhét have early cessation dates, while the rest of the country shows later cessation. In terms of LGP, mid-central areas have a longer period; southwestern parts have a shorter one, and the specific regions in Houaphan, Louangphrabang, and Xaignabouri have a shorter LGP. The northern regions generally have a longer LGP. However, the trends of all three indices were noted to be insignificant across the country.